Online Fake News, Elections and Role of Social Media Companies - Ms. Afeera Firdous (CISS Insight Journal, 2021)
Fake news and disinformation are not new tactics as in ancient times statesmen and rulers have used these techniques against their adversaries. Throughout the Cold War period, the US and Soviet Union also used disinformation against each other extensively. But now weaving of social media into peoples` life has made the demarcation of online and offline spaces increasingly unclear. This paper will discuss important terminologies such as ‘fake news’, ‘disinformation’, and ‘misinformation’ in online paradigm and also analyze how internet has changed the nature, intensity and reach of disinformation campaigns. Role and significance of online disinformation campaigns was brought into light during 2016 US presidential election. This paper will also examine the effects of online disinformation campaigns before and during general elections in different regions, particularly South Asia. International IT and social media companies had not taken into their consideration the threat of online disinformation with regards to elections until it became such an overwhelming phenomenon. After 2016 US Presidential Elections major international social media companies came together to cooperate for the mitigation of emerging challenge from online disinformation. But these companies failed to meet their pledge that online platforms will not be allowed to be used for spreading disinformation specifically information that may affect the General Election results in a country.